THE LEADERSHIP VALUES IN THE STORY OF THE PROPHET MUHAMMAD AS A RELIGIOUS LEADER AS WELL AS A STATE PERSPECTIVE AL-TAFSIR AL-MUNIR - Muhammad Romadoni; Bashori; Muhammad Arabiy (International Journal of Multidisciplinary Reseach, 2026)
This study examines the leadership values of the Prophet Muhammad as a religious leader as well as the state in the perspective of Tafsir al-Munir by Wahbah al-Zuhaili. The background of this research is the phenomenon of contemporary leadership crises characterized by corrupt practices, abuse of power, and weak moral integrity of leaders, so that there is a gap between the ideal concept of leadership and the existing reality. This research is a library research with a qualitative approach. Primary data were obtained from verses of the Qur'an that narrated the leadership of the Prophet Muhammad, namely Surah Ali 'Imran verses 121–129 and 159–164, al-Ahzab verses 9–11 and 26–27, al-Fath verses 4–7, and al-Hasyr verses 1–5 which were analyzed based on the interpretation of Wahbah al-Zuhaili in al-Tafsir al-Munir. Data analysis uses a narrative analysis method. The results of the study found five main leadership values: (1) the ability to maintain religion while managing world affairs in an integrated manner; (2) the enforcement of justice in each policy; (3) divine legitimacy as the foundation of state security; (4) wise decision-making in confusing situations with long-term orientation; (5) spirituality as a support for power. This study concludes that the leadership of the Prophet Muhammad offers an ideal leadership model that integrates spiritual and socio-political dimensions, which is relevant to addressing contemporary leadership crises.